The Kajian Penggunaan Alat Penangkap Ikan Cantrang di Wilayah Pengelolaan Perikanan Republik Indonesia - Sepri; Slamet Budi Prayitno (Jurnal Airaha, 2019)
Utilization of fish resources in Fisheries Management Area of the Republic of Indonesia, in some areas are in the fully exploited status can not be separated from the use of fishing gear that is not environmentally friendly and modifications to fishing gear. Fishing equipment potentially damaging marine life and the ecosystem is one of these fish is cantrang. Net withdrawal causes agitation bottom, causing a significant impact on the underwater ecosystem. This research is to see and study the problem of banning cantrang. Normative juridical approach, using secondary data, analyzed qualitatively and using deductive method to draw conclusions. Cantrang be categorized fishing gear damaging to the environment caused by the change of the structure of the fishing gear and operating techniques are not appropriate. Problems gear cantrang not lie in the appliance, but at the operational.